Synthesis, structure and reactivity of sulfur-rich [Fe(L1)(L2)("tpS4")] complexes with rigid [Fe("tpS4")] cores and σ-π co-ligands ("tpS4"2- = 1,2-bis(2-mercaptophenylthio)phenylene(2-); L1, L2 = CO, PR3, NO). - Sellmann, Dieter; Blum, David; Heinemann, Frank Wilhelm; Sutter, Jörg (European Journal of Inorganic Chemistry, 2003)
Optimization of synthesis and purifn. steps has made the new ligand tpS42- available in preparative amts. Treatment of FeCl2·4H2O with tpS4-Li2 or tpS4-Na2 yielded [Fe(tpS4)] (1), which in the solid state and in the absence of co-ligands probably trimerizes to give paramagnetic [Fe(tpS4)]3. The [Fe(tpS4)] fragment displays helical coordination of the tpS42- ligand and binds σ-π ligands CO, NO and phosphines to give diamagnetic 18-valence-electron [Fe(L1)(L2)(tpS4)]. The cis-dicarbonyl complex [Fe(CO)2(tpS4)] (2) is labile and readily dissocs. CO to give dinuclear [Fe(CO)(tpS4)]2 (3). Simultaneous coordination of CO and phosphines yielded [Fe(CO)(PR3)(tpS4)] with R = Me (4), Et (5), Pr (6) and Bu (7), but no reaction occurred with bulky PPh3 or PCy3 ligands. Bis(phosphine) complexes could be obtained only with PMe3 and the bidentate dppe, which yielded [Fe(PMe3)2(tpS4)] (8) and [Fe(dppe)(tpS4)] (11). Alkylphosphines with longer alkyl substituents, such as PPr3 and PBu3, gave the labile derivs. [Fe(PR3)2(tpS4)] with R = Pr (9) and Bu (10). 9 And 10 reversibly dissoc. one PR3 ligand, yielding diamagnetic [Fe(PR3)(tpS4)] fragments. These findings explain the decisive and hitherto inexplicable influence of PPr3 and PBu3 upon the stabilization of N2H2 in the diazene complexes [μ-N2H2Fe(PR3)(tpS4)2] with R = Pr, Bu. Treatment of (1) or (3) with NO or NO+ yielded [Fe(NO)2(tpS4)] (12). The mol. structures of 3, 4, 7 and 8 were detd. by x-ray structure anal. Spectroscopic and structural results indicate that the differences in reactivity between [Fe(L1)(L2)(tpS4)] and homologous [Fe(L1)(L2)(S4)] complexes can be traced back to subtle electronic and structural effects. [on SciFinder(R)]